2010
DOI: 10.1016/j.ygyno.2010.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of using human papillomavirus 16/18 genotype triage in cervical cancer screening

Abstract: Objective Testing for human papillomavirus (HPV) 16 and 18 genotypes, which are known to cause more than 65-70% of invasive cervical cancer cases, may allow clinicians to identify women at highest risk for underlying high-grade dysplasia missed by Pap cytology. Our objective was to determine the cost-effectiveness of adding HPV-16 and 18 genotype triage to current cervical cancer screening strategies in the United States. Methods We developed a lifetime Markov model to assess the cost-effectiveness of adding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 39 publications
2
21
0
1
Order By: Relevance
“…Kulasingam et al performed a study in Canada and found that a strategy with initial HPV DNA testing in women at 25 years was cost-effective (Kulasingam et al, 2009). Vijayaraghavan (2010) in the USA, expressed that implementing a program with HPV triage every three years after 30 years was the most costeffective strategy (Vijayaraghavan et al, 2010a).…”
Section: Comparison Of Starting Age Of Screeningmentioning
confidence: 99%
See 4 more Smart Citations
“…Kulasingam et al performed a study in Canada and found that a strategy with initial HPV DNA testing in women at 25 years was cost-effective (Kulasingam et al, 2009). Vijayaraghavan (2010) in the USA, expressed that implementing a program with HPV triage every three years after 30 years was the most costeffective strategy (Vijayaraghavan et al, 2010a).…”
Section: Comparison Of Starting Age Of Screeningmentioning
confidence: 99%
“…Berkhof et al (2010) in the Netherlands, indicated that starting screening with HPV triage with 5 years interval was the most cost effective strategies (Berkhof et al, 2010).Vijayaraghavan in South Africa reported that coscreening with HPV testing was less costly and the most effective strategy (Vijayaraghavan et al, 2009). Based on income we just found 5 articles in high income countries suggested starting age of screening below age 30 (Mandelblatt et al, 2002b;Kulasingam et al, 2009;Chuck, 2010;Vijayaraghavan et al, 2010a;Sroczynski et al, 2011)(Table1).…”
Section: Comparison Of Starting Age Of Screeningmentioning
confidence: 99%
See 3 more Smart Citations